Improvement Of the Process of Softening and Purification of Technical Water from Mechanical Mixtures (Journal of Pedagogical Inventions and Practices, 2021)
In the purification and softening of technical ways circulation water in our Republic and around the world taking into account the physicochemical-colloidal properties of water in purifying them from various metal ions mainly the separation of valuable chemical reagents and finely dispersed mechanical mixtures in water have been used. During the cooling or heating of raw materials of industrial water production enterprises, heat exchange increases the hydraulic resistance of process equipment as a result of cracking on the inner surface of the equipment, resulting in increased energy consumption, in addition to a decrease in heat and change of substances